2011
DOI: 10.1080/09645292.2010.547720
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early noncognitive skills on social outcomes in adolescence

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The analysis of the results confirmed H1, given that academic performance was mediated by the socio-emotional abilities of the students, fundamentally by decisionmaking. Other authors confirmed this result [5,11,14,25,28,[45][46][47][48]. Therefore, as stated by Sánchez [49], we confirmed that the role emotions play in an educational context is fundamental.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The analysis of the results confirmed H1, given that academic performance was mediated by the socio-emotional abilities of the students, fundamentally by decisionmaking. Other authors confirmed this result [5,11,14,25,28,[45][46][47][48]. Therefore, as stated by Sánchez [49], we confirmed that the role emotions play in an educational context is fundamental.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, we analyzed a set of variables that are considered necessary to adopt socially positive behaviors: self-awareness (the ability to look within oneself, concern for oneself and for how others perceive our appearance or actions), social awareness (the ability to become aware of the needs and problems of people in our family and social environment), self-management (the ability to manage autonomously), relationship management (the ability to maintain good relationships with others and use mechanisms or techniques that allow for obtaining and maintaining good relationships), and decision making (the process through which a choice is made between different options responsibly, analyzing the situation and evaluating the different options) [21,22]. According to Coneus and Laucht [28], the acquisition of these skills at an early age may increase the possibility of academic performance success.…”
Section: Introductionmentioning
confidence: 99%
“…Auld and Sidhu (2005) argue that failure to control for cognitive ability will confound the relationship between health and education. Noncognitive skills have also received considerable attention in recent studies (see, e.g., Heckman, Stixrud, and Urzua 2006;Heckman 2008) and have been linked to health and health-related behaviors (see, e.g., Carneiro et al 2007;Coneus and Laucht 2008;Keaster 2009;Cutler and Lleras-Muney 2010). Among these noncognitive skills, social adjustment is of particular relevance for schooling and health (Carneiro et al 2007).…”
Section: A Childhood Health and Parental Backgroundmentioning
confidence: 99%
“…Their implications for youth development are essential. Coneus and Laucht [ 15 ] suggested that the acquisition of such skills at early ages may prevent low academic performance, tobacco and alcohol use and risk behaviours such as delinquency. Delhaye et al [ 16 ] indicated that adolescents with depression or low resilience presented poorer socio-emotional skills.…”
Section: Introductionmentioning
confidence: 99%